2019
DOI: 10.1055/s-0039-1685502
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Extended-Spectrum β-lactamase, CTX-M-65 in Salmonella enterica serovar Infantis Isolated from Children with Diarrhea in Lima, Peru

Abstract: Gastroenteritis in children is a serious condition in many parts of the world. Salmonella enterica is one of the causes of the disease. In this study, 280 fecal samples from children with diarrhea in four hospitals in Lima, Peru, were collected between September 2012 and March 2013. Salmonella was detected in 26 of the samples. Serotyping demonstrated that 25 of the isolates were S. enterica Infantis, and one isolate was S. enterica Typhimurium. Repetitive extragenic palindromic–polymerase chain reaction analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
18
0
3
Order By: Relevance
“…29 The ESI clone, including the pESI plasmid and associated resistance and virulence genes, have been found in Europe and Asia, 9,10 and accounted for a majority of pediatric Salmonella cases in a study in Peru. 30 Furthermore, the potential spread of the pESI plasmid is of concern, as it has been successfully transferred to other enteric organisms, including other types of Salmonella. 31 Thus, the ESI clone and its associated pESI plasmid pose a continued public health problem deserving of further attention and study.…”
Section: Discussionmentioning
confidence: 99%
“…29 The ESI clone, including the pESI plasmid and associated resistance and virulence genes, have been found in Europe and Asia, 9,10 and accounted for a majority of pediatric Salmonella cases in a study in Peru. 30 Furthermore, the potential spread of the pESI plasmid is of concern, as it has been successfully transferred to other enteric organisms, including other types of Salmonella. 31 Thus, the ESI clone and its associated pESI plasmid pose a continued public health problem deserving of further attention and study.…”
Section: Discussionmentioning
confidence: 99%
“…The CTX‐M‐65 variant was detected in highly virulent S. Infantis isolates associated with a recent outbreak in the United States linked to travel to South America and unfit retail chicken meat (Brown et al, ). In South American countries, there are recent reports of MDR S. Infantis carrying bla CTX‐M‐65 in clinical samples from Ecuador and Peru (Cartelle Gestal et al, ; Granda et al, ), in wild owls in Chile (Fuentes‐Castillo et al, ), and in broiler poultry in Ecuador (Vinueza‐Burgos et al, ). This research suggests a link between poultry production and the observed human outbreaks; however, further research through WGS is needed to confirm this association.…”
Section: Discussionmentioning
confidence: 99%
“…microorganismos resistentes a estos antibióticos compromete su utilidad. Así, en algunas zonas, incluyendo diferentes regiones de Perú, los niveles de resistencia a los β-lactámicos más antiguos, como ampicilina bordea o supera el 90% (1,2) . Mientras, los niveles de resistencia a β-lactámicos más modernos, como cefalosporinas de 3ª y 4ª generación se sitúan alrededor del 50% (3) .…”
Section: Mensajes Claveunclassified
“…En gramnegativos el fenómeno de la resistencia a β-lactámicos se asocia principalmente a la producción de β-lactamasas. Entre estas, destacan por su elevada frecuencia las β-lactamasas tipo TEM, las cuales han sido profusamente reportadas en Perú (2,3) , aunque en la mayoría de las ocasiones sólo se ha determinado su presencia, sin desarrollar estudios de secuenciación que permitan determinar variantes.…”
Section: Mensajes Claveunclassified